The Opinion of the Italian Committee for Bioethics "Bioethical reflections on medically assisted suicide" - Sartea, Claudio (Medicina e Morale, 2019)
In July 2019 the Italian Committee for Bioethics approved and published an Opinion entitled "Bioethical reflections on medically assisted suicide". This paper, after a brief presentation of the institutional history of this document, seeks answers to some bioethical questions touched by the Opinion. What emerges is a critical reading that goes beyond individual questions (and especially the legal and juridical profiles involved), and refers to the need for a new meditation on the meaning of bioethics and its relationship with philosophical anthropology and identity issues.